Varieties of trade union protest - Gesine Höltmann; Endre Borbáth; Swen Hutter (Socio-Economic Review, 2025)
The article examines varieties of trade union protest across industrial relations regimes, using protest event data for 27 European countries between 2000 and 2021. We present a large-n analysis of how the level and `movement character' of union protest covaries with the strength and institutional settings of union movements across regimes. We show that unions remain important protest actors and that union protest in the public sphere notably outweighs workplace-related strikes. Furthermore, we find an inverse relationship between union institutionalization and the `movement character' of union protest: While strong union movements in highly institutionalized regimes display a strike-heavy repertoire, weaker union movements in contexts of low institutionalization rely heavily on protest actions beyond the workplace strike. With these findings, we provide a novel empirical assessment of what unions do in the protest arena and how institutional settings can be conducive to strike-heavy versus protest-heavy union tactics.
Keywords: 330; trade unions; social movements; industrial relations; strikes; civil society; Europe